The Relationship of the Beautiful Malino Event as an Effort to Increase the Tourist Visits - Muchlis Abbas; Ibrahim; Taufik Thahir; Muh.Fuad Randy; Masyadi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Tourism is one of the new styles of an industry that can provide rapid economic growth in terms of employment opportunities, income, standard of living, and activating other production sectors in tourist-receiving countries. to be of monetary value. This study aims to determine the relationship between implementing strategies in tourism events to increase the number of tourist visits. This study uses a descriptive quantitative approach with regression analysis to answer the hypothesis. This study takes data from a questionnaire distributed to 100 visitors, who are also the sample. The study's results stated that the beautiful Malino event positively and significantly affected tourist visits to Malino, Gowa Regency. Tourist visits increase from year to year, and this is due to the existence of several exciting activities held at the Beautiful Malino Event.